The parenthood gap: Firms and earnings inequality after kids - Rebecca Jack; Daniel Tannenbaum; Brenden Timpe (W.E. Upjohn Institute for Employment Research, 2025)
We document the dynamics of career paths around parenthood, capturing worker advancement within firms and across firms with differing pay rates. Using a new linkage between administrative data on U.S. workers' fertility and labor market histories, we show that the parental earnings gap is partly explained by mothers transitioning to lower-paying firms. Firm downgrading is driven by parents who take an extended absence from the labor force. Mothers who move to lower-paying firms see improved job amenities but less generous fringe benefits. The firm's contribution to the parental earnings gap rises over time and reaches one-third by the child's 11th birthday.
Keywords: J13; J16; J22; J31; 330; Parental earnings gap; employer-employee; fertility; lower-paying firms; reallocation